Evaluation of interannual variability of Arctic and Antarctic ozone loss since 1989 - Goutail, Florence; Pazmino, Andrea; Pommereau, Jean-Pierre; Lefèvre, Franck; Godin-Beekmann, Sophie; Hauchecorne, Alain; Lecouffe, Audrey; Clerbaux, Cathy; Boynard, Anne; Hadji-Lazaro, Juliette; Chipperfield, Martyn; Feng, Wuhu; et al. (2021)
Ozone depletion over Polar Regions is monitored each year by satellite and ground-based instruments. The first signs of healing of the ozone layer linked to the decrease of ozone destructive substances (ODSs) were observed in Antarctica using different metrics (ozone mean values, ozone mass deficit, area of the ozone hole) and simple or sophisticated models. Chemistry climate models predict that climate change will not affect expected ozone recovery over Antarctica but will accelerate recovery in the Arctic due to the possible enhancement of the Brewer Dobson circulation. However, ozone loss observations by SAOZ UV-Vis spectrometers do not show a clear sign of recovery in the latter region. In addition, a record of 38% ozone loss in 2010/2011 and 2019/2020 was estimated. In this study, the vortex-averaged ozone loss in the last three decades will be evaluated for both Polar Regions using the passive ozone tracer of two chemical transport models (REPROBUS and SLIMCAT CTMs) and total ozone observations from SAOZ and satellite observations (IASI/METOP and Multi-Sensor Reanalysis (MSR-2)). The tracer method allows us to determine the evolution of the daily rate of ozone destruction, and the amplitude of the cumulative loss at the end of the winter. The cumulative ozone destruction in the Artic varies between 0-10% in relatively warm winters with short vortex duration to up to 25-38% in colder winters with longer vortex persistence, while in Antarctica it is mostly stable, around 50%. Interannual variability of 10-days average rate will be analyzed and compared between both hemispheres as well as the timing to reach different thresholds of absolute ozone loss values. Finally, linear trend of ozone loss and temperature since 2000 will be estimated in both Polar Regions in order to evaluate possible ozone recovery.
Keywords: Antarktis; klimaendringer; miljøovervåking; ozonlaget; polarområdene

Norway and the Antarctic - Stephenson, Robert B; [Barr, Susan] (The Erebus and Terror Press, 2017)
Keywords: Antarktis; Nordmenn; norske ekspedisjoner; polarfarere

Forskrift om miljøvern og sikkerhet i Antarktis - miljødepartementet, Klima- og (Lovdata, 2013)
Keywords: Antarktis; Dronning Maud Land; forurensning; forvaltning; jus; miljøvern; naturvern

Forskrift om miljøvern og sikkerhet i Antarktis - Miljøverndepartementet (Justisdep., 2013)
Keywords: Antarktis; jus; miljøvern

Roald Amundsens sydpolsferd (1910-1912) = Roald Amundsen's South Pole expedition (1910-1912) - Amundsen, Roald; Diesen, Jan Anders; Lund, Harald Østgaard (Norsk filminstitutt, 2010)
Keywords: Antarktis; Fram (skip); Norge; Sydpolen; Sydpolsekspedisjonen; dokumentarfilmer; ekspedisjonsfilmer; oppdagelsesreiser; polarområdene

Samtykke til ratifikasjon av Protokoll om miljøvern til Antarktistraktaten, undertegnet i Madrid 4. oktober 1991 - Utenriksdepartementet (1992)
Keywords: Antarktis; forvaltning; miljøvern; politikk

Journal over den Belgiske Sydhavs-Expedition 97-99 - Koren, Johan (1988)
Keywords: Antarktis; Belgica (skip); dagbok; oppdagelsesreiser; overvintring; polarekspedisjoner

Iceberg discharge and the mass balance of Antarctica - Orheim, Olav (National Academy Press, 1985)
Keywords: Antarktis; glasiologi; innlandsis; isberg; isbreer

Adaptation to low temperature in Antarctic terrestrial arthropods - Sømme, Lauritz (Comite National Francais Des Recherches Antarctiques, 1982)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Polarområdenes økosystemer - Larsen, Thor (1978)
Keywords: Antarktis; polarområdene; økologi

The work of SCAR for the conservation of nature in the Antarctic - Gjelsvik, Tore (University of Chile, 1977)
Keywords: Antarktis; fauna; flora; forurensning; kongress; miljø; politikk; symposium; økologi

Global glacier mass balance variations during the past 300 years - Orheim, Olav (Arctic Institute of North America, 1977)
Keywords: Antarktis; glasiologi; is; isbreer; klimaendringer; konferanse; polarområdene; stratigrafi; symposium

Norwegian Antarctic Research. Past and Present. - Orheim, Olav (University of Chile, 1977)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner; Weddellhavet; geologi; glasiologi; havis; hvalfangst; kongress; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; symposium

Past and present mass balance variations and climate at Deception Island, South Shetland Islands, Antarctica - Orheim, Olav (International Association of Hydrological Sciences, 1975)
Keywords: Antarktis; forskning; glasiologi; klimatologi

Svalbard - Jan Mayen - The Antarctic Possessions (Utenriksdepartementet, 1973)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene

En del sovjetiske forskningsinstitusjoner, med særlig vekt på de som arbeider med oppgaver i arktiske og antarktiske strøk - Heintz, Natascha ([Norsk Polarinstitutt], 1965)
Keywords: Antarktis; forskning; polarområdene; vitenskap

Antarktiske fugler - Holgersen, Holger (Stavanger Museum. Naturhistorisk avdeling, 1949)
Keywords: Antarktis; Dronning Maud Land; fugler; ornitologi; zoologi

Antarktis/Antarctica: Kart nummer 7 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Antarktis; Lars Christensen; ekspedisjoner; flyfoto; geografi; kartlegging; luftfoto

Atlas over dele av det antarktiske kystland = Atlas of parts of the Antarctic coastal lands - Hansen, Hans Edvard; Luncke, Bernhard (Grøndahl, 1946)
Keywords: Antarktis; Lars Christensen; Sørishavet; Thorshavn ekspedisjon; flyfoto; kartlegging; luftfoto

Who discovered Antarctica? - Aagaard, Bjarne (1939)
Keywords: Antarktis; historie; historikk; oppdagelsesreiser

Antarktis og Sydishavet (Norwegian Mapping Authority / Kartverket, 1936)
Keywords: Antarktis; Jason ekspedisjonene; Norvegia ekspedisjoner; Odd I; Sørishavet; Thorshavn ekspedisjon; ekspedisjonen; geografi; kartlegging

Atlas over Antarktis og Sydishavet : utgitt av Hvalfangernes Assuranceforening i anledning av foreningens 25-års jubileum - Hansen, Hans Edvard (red.) (Hvalfangernes Assuranceforening, 1936)
Keywords: Antarktis; Nordmenn; Norge; Sørishavet; hvalfangst; kartlegging; norske ekspedisjoner; oppdagelsesreiser

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1935)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1933)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 3) (Hvalfangernes Assuranceforening, 1933)
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

Omkring Löitnant Shirase's Sydpolarexpedition 1910-12 - Hamre, Ivar ([forfatteren], 1932)
Keywords: Antarktis; Choku Shirase; Den japanske antarktisekspedisjonen 1910–12; Sydpolen; ekspedisjoner; oppdagelsesreiser

Norvegia-ekspedisjonen 1930-1931 (Norges geografi oppmåling, 1931)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII hav (Norges geografi oppmåling, 1931)
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

[Kart over Antarktika og Sydishavet]. Skisser med "Odd" og "Norvegia" sine ruter i Antarktis 1927-1929 - [Aagaard, Bjarne] (1929)
Keywords: Antarktis; Norvegia ekspedisjoner; Odd I; Sørishavet; ekspedisjonen; geografi; kartlegging

Dagbok: "Den tredje Framfærd. 7de juni 1910 - 6de mars 1912" - Amundsen, Roald (Nasjonalbiblioteket, 1912)
Keywords: Antarktis; Roald Amundsen; Sydpolen; dagbøker; ekspedisjoner; oppdagelsesreiser

"Dagbog tilhørende Fredrik Hjalmar Johansen, ført på 3die Framexpedition, påbegyndt efter afgangen fra Norge, 15de august 1910 til 14de januar 1912" - Johansen, Hjalmar (Nasjonalbiblioteket, 1912)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; oppdagelsesreiser

Parry Mountains - Collier, William; Borchgrevink, Carsten Egeberg
Keywords: Antarktis; Southern Cross; ekspedisjonen; geografi; kartlegging

Robertson Bay, South Victoria Land - Collier, William; Borchgrevink, Carsten Egeberg
Keywords: Antarktis; Southern Cross; ekspedisjonen; geografi; kartlegging

Southern Cross from Hobart to Cape Adare - Collier, William; Borchgrevink, Carsten Egeberg
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; ekspedisjonen; geografi; kartlegging

Polar Ponies: The Forgotten Story of Antarctica’s Meat-Eating Horses - O’Reilly, CuChullaine (The Long Riders Guild Academic Foundation)
While it is now commonly agreed that dog travel in winter conditions is an excellent methodology, abundant evidence demonstrates that this view was not shared by all polar explorers at the beginning of the last century. What has also been overlooked is the simultaneous use of meat-eating horses in trying to reach both the North and South Poles.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Journal over flyvninger utført under Lars Christensens ekspedisjon 1936/37 - Romnæs, Nils
Keywords: Antarktis; Thorshavn ekspedisjon; flyfoto; flyvninger; kartlegging; luftfoto